Exploring a modified quantum dynamics based on Tsallis' distribution - Chung, Won Sang; Junker, Georg; Nieto, Luis M.; Hassanabadi, Hassan (Physics Letters A, 2025)
In this paper, inspired by Tsallis' probability distribution based on a q-deformed Boltzmann factor, we stipulate a new q-deformed quantum dynamics by applying the inverse Wick rotation β→it to the Tsallis-deformed Boltzmann factor. We obtain a new time-dependent q-deformed Schrödinger equation. The free time-evolution of a Gaussian wave packet and that induced by an harmonic interaction are studied within this q-deformed quantum mechanical framework.
CRIS-Team Scopus Importer:2025-10-16